Cybersecurity Best Practices: Strategies for Protecting Organizations from Cyber Threats (International Journal of Engineering and Computer Science, 2023)
The academic and practitioner literature on the topic of information security is extensive. The majority of the study is concentrated on finding technology remedies to security threats, however other methods like deception, reaction, detection, and deterrent are also being considered. This article presents the results of a qualitative study that was carried out in Korea with the aim of discovering the security measures that companies employ to safeguard their information systems. Based on the findings, it is clear that there is a widespread ignorance of business security issues and a strong emphasis on taking precautions to guarantee the availability of services and technologies. There were additional strategies, but they were all preventative. With an emphasis on integrating, balancing, and optimizing systems, the paper lays forth a research agenda for implementing various techniques across a company. This study examined a wide range of issues, including data protection and potential meeting places for security strategy discussions, like military archives. In all, nine different security measures have been recognized. The utilization of various security techniques in enterprises is investigated through a qualitative focus group approach. The goal of the focus groups was to get the security managers from eight different companies to talk about the security measures their companies take. The results show that many companies take precautions to ensure that their technological services are always available. In order to back up the prevention strategy operationally, some of the other methods that were identified were utilized.